Nilai Religius dalam Cerita Rakyat Mbah Rogo Moyo di Kabupaten Kudus - Muzdalifah, Muzdalifah; Nabila, Mufthiri Silma; Aulia, Miftahul; Amelia, Nasywa Azka; Kanzunnudin, Mohammad (Edu Berkah Khatulistiwa, 2024)
The purpose of this research is to analyze the structure of Axel Olrix and the religious value contained in the story of Mbah Rogo Moyo. This research uses qualitative research methods. Regarding the source of data comes from a book entitled